ChemInform Abstract: Synthesis of Novel Imidazopyrrolo‐Fused Isoxazole Derivatives Through Acid‐Mediated Intramolecular 1, 3‐Dipolar Cycloaddition. Issue 42 (28th September 2016) - Xu, Yin; Wang, Fukai; Li, Jiling; Shao, Xusheng; Xu, Xiaoyong; Li, Zhong
Abstract: starting from various nitromethylene‐imidazolidine derivatives